Tandem thionation of biomass derived levulinic acid with Lawesson's reagent. Issue 10 (18th April 2016) - Li, Zheng; Tang, Xing; Jiang, Yetao; Zuo, Miao; Wang, Yangjun; Chen, Wei; Zeng, Xianhai; Sun, Yong; Lin, Lu
Abstract : Tandem thionation of off-the-shelf and crude levulinic acid is performed with Lawesson's Reagent (LR) to generate biomass derived thiophenic compounds. Abstract : Herein we report a tandem thionation of biomass derived levulinic acid (LA) to generate thiophenic compounds. LA is initially converted to several thiophenones and then an aromatic di-thionated product, 5-methylthiophene-2-thiol, is obtained with the highest yield of 78%. An overall synthesis of thiophenic products from cellulose is also developed.